DEVELOPMENT OF E-MODUL BASED ON HIGH ORDER THINKING SKILL PROBLEM WITH STUDENTS TEAM ACHIEVEMENT DIVISION OF LEARNING MODEL IN ALGEBRA - Imam Muhajir Setiawan; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
The lack of media and learning facilities, and the lack of Higher Order Thinking Skills (HOTS) questions, makes learning less exciting and monotonous. This study aims to develop e-modules based on HOTS questions with Student Team Achievement Division (STAD) learning models and determine the quality of e-modules developed. This study refers to the ADDIE model with Analyze, Design, Development, Implementation, and Evaluation stages. This study's subjects were teachers and 7th-grade students of Junior High School (SMP) Muhammadiyah Ngemplak and SMP Negeri 2 Ngemplak. This study's object is an e-module based on HOTS questions with STAD learning models on algebraic form material. Data collection techniques using a questionnaire assessment by material experts, media experts, and students. Data analysis techniques in the form of qualitative descriptive analysis and quantitative descriptive. The results showed that material experts in the aspects of conformity, completeness, convenience, and clarity received values of 86%, 80%, 87%, and 88%, respectively. The media experts in effectiveness, ease, suitability, completeness, and communicative and interactive scores were 93%, 93%, 92%, 90%, and 92%. The average results of student responses from the two schools on convenience, clarity, suitability, appearance, attractiveness are 90%, 90%, 90%, 94%, and 92%. So it can be concluded that the e-module produced is classified both in terms of material, very good in terms of media, and very practical in its use.